2019
DOI: 10.1016/j.chemosphere.2018.09.118
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms of miR-96 and miR-184 abnormal expressions on otic vesicle development of zebrafish following exposure to β-diketone antibiotics

Abstract: Chronic ototoxicity of β-diketone antibiotics (DKAs) to zebrafish (Danio rerio) was explored in detail by following abnormal expressions of two hearing-related miRNAs. Dose-dependent down-regulation of miR-96 and miR-184 was observed in otoliths during embryonic-larval development. Continuous DKA exposure to 120-hpf larva decreased sensitivity to acoustic stimulation. Development of otolith was delayed in treatment groups, showing unclear boundaries and vacuolization at 72-hpf, and utricular enlargement as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Wang and co-workers provided important information concerning the joint effects of β-diketone antibiotic mixture exposure on zebrafish. They demonstrated that the exposure to fluoroquinolones and tetracyclines can induce dysfunction of the immune system, liver and heart; damage the antioxidant defense system; and cause reproductive failure, skeletal disorders and neurotoxicity effects [ 30 , 31 , 35 , 37 , 112 , 113 , 114 ]. Briefly, treatments with DKAs affect a variety of cellular and biological processes in zebrafish.…”
Section: Effects Of Antibiotic Mixtures In Zebrafishmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang and co-workers provided important information concerning the joint effects of β-diketone antibiotic mixture exposure on zebrafish. They demonstrated that the exposure to fluoroquinolones and tetracyclines can induce dysfunction of the immune system, liver and heart; damage the antioxidant defense system; and cause reproductive failure, skeletal disorders and neurotoxicity effects [ 30 , 31 , 35 , 37 , 112 , 113 , 114 ]. Briefly, treatments with DKAs affect a variety of cellular and biological processes in zebrafish.…”
Section: Effects Of Antibiotic Mixtures In Zebrafishmentioning
confidence: 99%
“…Additional studies proved that treatments with β-diketone antibiotic mixtures led to abnormal development of otoliths in zebrafish embryos and a decreased sensitivity to acoustic stimulation, which implies the occurrence of hearing impairment [ 31 ]. Notably, the miR-96 and miR-184 were identified as key factors regarding the molecular mechanisms regulating hearing functions.…”
Section: Effects Of Antibiotic Mixtures In Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, miR-19 was reported to directly target the TGFβ pathway associated with the inflammation pathway (Li et al, 2012), whereas the miR-130a-fabp3 pair was reported to play a vital role in the PI3K/AKT-mTOR pathway (Chen et al, 2018). Recent studies reported that miR-96 was important in otic vesicle development, involved in the hearing process, along with miR-183 (target mfap4) (Li et al, 2010;Kim et al, 2018), and in the formation of the nervous system in conjunction with miR-184 (Li et al, 2016(Li et al, , 2019. LncRNA UCA1 promotes cell proliferation by upregulating Foxo3 and downregulating miR-96 (Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…subsequently, Li et al (105) conducted an in vivo study on zebrafish embryos to evaluate the association between β-diketone antibiotic-induced ototoxicity and the regulatory role of miRNAs in hearing. Firstly, they noted a decreased response to acoustic stimuli in the treatment group compared to the controls.…”
Section: Mirnas and Drug-induced Ototoxicitymentioning
confidence: 99%